Community water management and agricultural extension services: effects, impacts and perceptions in the coastal zone of Bangladesh - Buisson, Marie-Charlotte; Saikia, Panchali; Maitra, S. (International Water Management Institute, 2020)
The coastal region of Bangladesh is prone to natural disasters and these events are expected to worsen as a result of climate change. Combined with anthropogenic factors, these events challenge livelihood opportunities, especially crop production. Waterlogging, tidal activity and the lack of proper drainage facilities are major constraints to agricultural production in these areas. The CGIAR Research Program on Water, Land and Ecosystems (WLE) tested, at pilot scale, the combination of innovative agricultural technologies with improved water management to overcome these challenges. This report assesses this intervention by observing the effects, measuring the short-term impacts and understanding the perceptions. The results highlight the need to integrate the interventions into the local context, and acknowledge that institutions and markets need to mature to harness the benefits from innovations. It also underlines the potential of multi-scale interventions combining plot-level and farmer-led innovations, community management and rehabilitation of large schemes.